The Provision of Quality Municipal Water Services to Communities in Nelson Mandela Bay - Oyelana, Akeem Adewale; Malandiswe , Nteya; Jakoet-Salie, Amina (Brawijaya University, 2024)
This study investigated the barriers the Nelson Mandela Bay Municipality (NMBM) faces in delivering quality water service. This paper employed a desktop research. Data were collected using secondary data. The data collected were analysed using thematically analysis. The study's findings show that the NMBM faces various barriers to providing adequate quality water service. The study noted severe backlog challenges, including, among others, the ageing infrastructure and financial constraints perpetuated by corruption. The study established that the NMBM does not supply quality water services to communities due to poor accountability and massive corruption in the NMBM. Therefore, this study recommends that municipalities recruit adequately-skilled personnel to run the NMBM’s water supply service affairs.